Status preferences and optimal corrective taxes: A note - Klaus Beckmann; Susan Gattke (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2008)
We take issue with the argument expounded, among others, by Layard (2006, Economic Journal) that status-seeking preferences justify heavier taxation of income because this serves to internalise the negative externality that the pursuit of status imposes on others. In a model where status depends on both income and effort, we show that the optimal corrective tax rate is smaller than if non-monetary status plays no role, and that a subsidy of work effort at the margin may be called for. Additionally, we demonstrate how the elasticity of labour supply depends on the parameters of the status production function in such a model, and discuss potential implications for optimal income taxation.
urn:nbn:de:gbv:705-opus-17253
Keywords: D1; D3; H2; 330; Sozialer Status; Präferenztheorie; Einkommensteuer; Optimale Besteuerung; Arbeitsangebot; Elastizität; Theorie